Chebulagic Acid, a Hydrolyzable Tannin, Exhibited Antiviral Activity in Vitro and in Vivo against Human Enterovirus 71 - Yang, Yajun (Molecular Diversity Preservation International (MDPI), 2013)
Human enterovirus 71 is one of the major causative agents of hand, foot and mouth disease in children under six years of age. Presently, no vaccines or antiviral drugs have been clinically available to employ against EV71. In this study, we demonstrate that treatment with chebulagic acid reduced the viral cytopathic effect on rhabdomyosarcoma cells with an IC(50) of 12.5 μg/mL. The utilization of the chebulagic acid treatment on mice challenged with a lethal dose of enterovirus 71 was able to efficiently reduce mortality and relieve clinical symptoms through the inhibition of viral replication. Chebulagic acid may represent a potential therapeutic agent to control infections to enterovirus 71.